Human Cardiac Ventricular‐Like Organoid Chambers and Tissue Strips From Pluripotent Stem Cells as a Two‐Tiered Assay for Inotropic Responses. Issue 2 (28th March 2019) - Keung, Wendy; Chan, Patrick K.W.; Backeris, Peter C.; Lee, Eugene K.; Wong, Nicodemus; Wong, Andy O.T.; Wong, Gabriel K.Y.; Chan, Camie W.Y.; Fermini, Bernard; Costa, Kevin D.; Li, Ronald A.
Abstract : Traditional drug discovery is an inefficient process. Human pluripotent stem cell‐derived cardiomyocytes can potentially fill the gap between animal and clinical studies, but conventional two‐dimensional cultures inadequately recapitulate the human cardiac phenotype. Here, we systematically examined the pharmacological responses of engineered human ventricular‐like cardiac tissue strips (hvCTS) and organoid chambers (hvCOC) to 25 cardioactive compounds covering various drug classes. While hvCTS effectively detected negative and null inotropic effects, the sensitivity to positive inotropes was modest. We further quantified the predictive capacity of hvCTS in a blinded screening, with accuracies for negative, positive, and null inotropic effects at 100%, 86%, and 80%, respectively. Interestingly, hvCOC, with a pro‐maturation milieu that yields physiologically complex parameters, displayed enhanced positive inotropy. Based on these results, we propose a two‐tiered screening system for avoiding false positives and negatives. Such an approach would facilitate drug discovery by leading to better overall success.